Vocabulary acquisition through word Association as a tool to enrich translator's lexical repertoire. - Arce Ardila, Bolívar Andrés (2015)
The role of translators is of major importance to bridge the communication gap among the peoples of the world. This profession requires a lot of skill, hard work, and determination to meet the needs of translation users. For this reason, translators must possess a number of professional traits including proficiency in languages in addition to a growing willingness to continue improving their skills. In order to help Proz.com¿s Ecuadorian translators, the world¿s largest online translation network, in the pursuit of excellence and after a qualitative analysis of their vocabulary knowledge and their vocabulary learning processes, it is advisable for them to acquire new, functional vocabulary and make drastic changes to their vocabulary acquisition techniques. The purpose of this thesis work is to provide a new, powerful tool of vocabulary learning process in order to help Proz.com¿s Ecuadorian translators to develop an extensive vocabulary repertoire through word association in an efficient and unconventional manner.